Reduced risk for chronic myelogenous leukemia in individuals with the cytochrome P-450 gene polymorphism CYP1A1*2A - Löffler, Harald; Bergmann, Jörg Stefan; Hochhaus, Andreas; Hehlmann, Rüdiger; Krämer, Alwin (Blood, 2001)
Most cancers can be attributed to environmental factors that act in conjunction with both genetic and acquired susceptibility.1 It has been suggested that individuals possessing a modified ability to metabolize carcinogens are at increased risk for cancer.1 In fact, germ-line polymorphisms of genes encoding carcinogen-metabolizing enzymes, namely, phase I cytochromes P-450 (CYPs) and phase II glutathione S-transferases (GSTs), have been shown to influence the risk of a variety of disorders thought to be caused by environmental exposure to toxic agents, including Parkinson disease2 and cancers of the gastrointestinal tract, skin, bladder, cervix, and lung.13 In contrast to these solid tumors, the etiologic role of chemical carcinogens is less obvious for many hematologic malignancies. Nevertheless, Krajinovic et al4 reported theGSTM1 null and CYP1A1*2A genotypes to be risk factors for childhood acute lymphoblastic leukemia (ALL), and myelodysplastic syndromes (MDSs) seem to be associated with theGSTT1 null genotype.5